Nuevas formas de narrativa en la literatura polaca - Krupka, Pawel (Eslavística Complutense, 2004)
Lately a new form of fiction has developed in Poland. It is a fusion of elements of a traditional novel, of a philosophical essay and of various lyrical expressions. In this article the motivations and the mechanism of development of this new literary form are analysed on the example of three books, that appeared recently on Polish editorial market.
Keywords: Poland; Literary form; Novel; Essay; Lyrical expressions